Unraveling Philosophical Justice in Judges’ Decisions on Marital Property Disputes: A Jurimetric Analysis - Nenan Julir; Jayusaman Jayusaman; Khairunnisa Khairunnisa; Humaidulloh Humaidulloh; Ai Ulfaturrosydah; Agusti Yelpi (Jurnal Madania)
This study is aimed at analyzing the Jurimetrcs of the decision Number: 0420/Pdt.G/2017/PA.Mt dealing with marital property disputes suspected of failing to fulfill the sense of justice of the disputing couple. The method used in this study is qualitative content analysis, analyzing documents and texts of court judge decisions. Qualitative content analysis identifies, processes, and describes the judge's decision, then relates it to society's social and cultural context. The analysis of this study revealed that the judge's decision was only guided by the Compilation of Islamic Law article 97; if a husband and wife divorced, each of them would get half of the marital property, without considering the wife's position as the main breadwinner and the portion of duties and obligations in the family. Jurimetric analysis of the decision is considered to create a sense of justice. In the context of distributing marital property in Indonesia, Jurimetrcs can assist judges in determining the value of the share of joint property for each husband and wife after an equitable divorce.